2010
DOI: 10.1111/igc.0b013e3181bdbeb5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pulmonary Embolism Including Asymptomatic Cases in Gynecologic Oncology

Abstract: A substantial number of postoperative PEs were occult, and identification of high-risk patients and routine SpO2 level monitoring would reduce the diagnostic delay of PE after gynecologic surgery. Increasing age, longer operation time, and obesity were risks. The use of a perioperative intermittent pneumatic compression device in multimodal conditions might thus prevent PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…6,16 In our previous study, which included the period before methodical prophylaxis was established, the overall incidence of postoperative PE was 2.14%; according to univariate analysis, the incidence was higher in women with malignant diseases than in women with benign diseases. 3 However, in the present study, the incidence of postoperative PE did not statistically differ between women with malignant diseases and those with benign diseases, although the mean age was significantly older and the mean operation time was significantly longer among women with malignant diseases. The rate of anticoagulant use and the rate of D-dimer measurement were both significantly higher among women with malignant diseases compared with those with benign diseases.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…6,16 In our previous study, which included the period before methodical prophylaxis was established, the overall incidence of postoperative PE was 2.14%; according to univariate analysis, the incidence was higher in women with malignant diseases than in women with benign diseases. 3 However, in the present study, the incidence of postoperative PE did not statistically differ between women with malignant diseases and those with benign diseases, although the mean age was significantly older and the mean operation time was significantly longer among women with malignant diseases. The rate of anticoagulant use and the rate of D-dimer measurement were both significantly higher among women with malignant diseases compared with those with benign diseases.…”
Section: Discussioncontrasting
confidence: 73%
“…2 Following gynecologic surgeries, another study found that 35.6% of women diagnosed with postoperative PE were asymptomatic and had no signs except for a low oxygen saturation as measured by pulse oximetry (SpO 2 ) level. 3 The PE was mainly diagnosed by lung scan in these studies, [1][2][3] and subsegmental PE cases were hard to precisely diagnose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using computed tomography pulmonary angiography (CTPA), which has better spatial resolution and diagnostic accuracy than a ventilation-perfusion (V/Q) scan, small (asymptomatic) perfusion defects can be detected more accurately [40, 41]. If these perfusion defects are taken into account, the incidence of asymptomatic PE after non-cardiac surgery is expected to exceed 4 % [37, 42, 43]. However, the clinical relevance of small—mostly asymptomatic - perfusion defects has not yet been fully determined [44].…”
Section: Literaturementioning
confidence: 99%
“…Rates are higher in ovarian cancer and with prolonged or complicated surgeries, but are still generally below 10%. Risk of PE also increases with age over 60 years and every BMI increase of 5 kg/m 2 [11]. Treatment of VTE includes hemodynamic support, supplemental oxygen and therapeutic levels of anticoagulation within 24 h. In acute PE, thrombolytic therapy and/or intubation may be initiated.…”
Section: Venous Thromboembolismmentioning
confidence: 99%